Stella's Existence Reflected In 30 Days Of Night: Dark Daysmovie (2010) Directed By Ben Ketai: An Existentialist Approach - Widyaningsih, Widyaningsih (2012)
This study is aimed to show Stella's existence in 30 Days of Night: Dark Days movie by using existentialist approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the Existentialist Approach. This research is descriptive qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is the 30 Days of Night: Dark Days movie directed by Ben Ketai released in 2010. While the secondary data sources are othermaterials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene,cinematography, sound, and editing are related to each other and form a unity.Second, based on the Existentialist analysis reflected in the character and characterization in being, existence before essence, consciousness (cogito), freedom to choose, anxiety, transcendence ego,and nothingness, awareness of the existence of life lead to meaningful goal in human's life.